Doskonalenie jakości obsługi klienta w administracji samorządowej na przykładzie Urzędu Miasta Zakopane - Czernecka, Marzena (My University, 2014)
Wdrożenie systemu zarządzania jakością w administracji samorządowej daje możliwość zwiększenia skuteczności działania. Odbywa się to poprzez wyeliminowanie działań niepotrzebnych i procesów powielanych w pracy urzędu. Zapobiega powstałym problemom i niezgodnościom oraz zapewnia pracownikom urzędu przejrzysty i zrozumiały zakres uprawnień, obowiązków i odpowiedzialności. Badania empiryczne przeprowadzono w Urzędzie Miasta Zakopane w trzech etapach. Zastosowano kwestionariusz ankiety i wywiady bezpośrednie. Analiza wyników obnażyła obszary, na których konieczne jest wprowadzenie usprawnień i zmian, głównie w zakresie: struktury organizacyjnej, sprawnego przepływu informacji, komunikacji wewnątrzorganizacyjnej, obsługi klientów, strony internetowej i obsługi petentów drogą elektroniczną,. Pracę Urzędu Miasta Zakopane oceniono korzystnie. Pracownicy dokonują wszelkich starań, aby jakość świadczonych usług była na wysokim poziomie. Można zatem stwierdzić, że Urząd Miasta Zakopane pozytywnie kreuje i umacnia swój wizerunek, jako dobrze zarządzającej organizacji.

The implementation of a quality management system in local government administration opens up the possibility to increase efficiency. This is achieved by eliminating any unnecessary operations or duplicate processes in the work of the authority. It prevents the resultant problems and discrepancies, and provides the office workers with a clear and comprehensible range of powers, duties and responsibilities. The empirical research was conducted in Zakopane City Council Office in three stages. A questionnaire survey and personal interviews were used. Analysis of the results revealed the areas in which it was necessary to introduce improvements and changes, primarily in the area of the organizational structure, the smooth flow of information, the communication within the organization, the customer service, the website and handling of applicants electronically. The work of Zakopane City Council Office was evaluated favourably. The employees make every effort to ensure the service provided is of the highest quality. It can therefore be concluded that Zakopane City Council creates and reinforces a positive image of a well managed organization.
Improving the quality of customer service in local government administration based on the example of Zakopane City Council
Keywords: system zarządzania jakością; jakość; ISO; administracja publiczna; urząd; działalność usługowa; quality management system; quality; ISO; public administration; authority; services